2017
DOI: 10.1016/j.ypmed.2017.08.024
|View full text |Cite
|
Sign up to set email alerts
|

To vape or not to vape? Effects of exposure to conflicting news headlines on beliefs about harms and benefits of electronic cigarette use: Results from a randomized controlled experiment

Abstract: News coverage of novel tobacco products including e-cigarettes has framed the use of these products with both positive and negative slants. Conflicting information may shape public knowledge, perceptions of e-cigarettes, and their harms. The objective of this study is to assess effects of exposure to conflicting news coverage on US adults’ beliefs about harms and benefits of e-cigarette use. We conducted a one-way between-subjects randomized controlled experiment in 2016 to compare the effects of viewing eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 33 publications
2
26
1
Order By: Relevance
“…The finding that exposure to mostly negative valence news stories was more likely to be associated with perceptions that e-cigarettes cause harm (compared to positive news) is consistent with an experimental study which found that exposure to negative e-cigarette news headlines increased beliefs about e-cigarette harms compared with exposure to positive headlines (7). Past 30 day e-cigarette users exposed to mostly negative e-cigarette news also had higher odds of intending to quit e-cigarettes in the next month.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The finding that exposure to mostly negative valence news stories was more likely to be associated with perceptions that e-cigarettes cause harm (compared to positive news) is consistent with an experimental study which found that exposure to negative e-cigarette news headlines increased beliefs about e-cigarette harms compared with exposure to positive headlines (7). Past 30 day e-cigarette users exposed to mostly negative e-cigarette news also had higher odds of intending to quit e-cigarettes in the next month.…”
Section: Discussionsupporting
confidence: 83%
“…News coverage may also inform the public about the potential risks and benefits of tobacco products including e-cigarettes, which may impact public perceptions and product use intentions (7,8). Indeed, one experimental study found that participants who viewed negative e-cigarette news headlines reported increased beliefs about e-cigarette harms and lower beliefs about benefits compared with those exposed to positive headlines (7). This is relevant given that recent content analysis research found e-cigarette news stories to more frequently discuss potential e-cigarette risks versus benefits (e.g., use for harm reduction) (1).…”
Section: Introductionmentioning
confidence: 99%
“…This may stem in part from media coverage, which has presented a mixed picture of the potential risks and benefits associated with the products and focused on regulatory policies for ecigarettes (Yates et al, 2015). Experimental exposure to (Tan, Lee, Nagler & Bigman, 2017), as well as recalling more exposure to (Tan, Bigman, Mello, & Sanders-Jackson, 2015) negative information about e-cigarettes is associated with perceiving greater health risks from SHVe. As scientific evidence accumulates and policies are implemented, it will be important to assess effects of regulatory and information environments on the public's beliefs and behaviors with regard to tobacco and tobacco-related products.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of smoking status, a significant proportion of US adults mistakenly believed that nicotine is the primary disease-causing chemical [ 30 ]. Studies also found that news articles discussed potential harms or risks of ENDS more often than their potential benefits [ 31 ], which may increase beliefs about ENDS harms while reducing beliefs about benefits [ 32 ]. Given the mixed evidence on ENDS warning messages and the complexity surrounding the perceptions of ENDS, it is critically important to assess how consumers may interpret messages from the FDA addiction warning and manufacturers’ voluntary warnings, and to what extent these messages may influence consumers’ harm perceptions about ENDS.…”
Section: Introductionmentioning
confidence: 99%